INFLUENCE OF ANTIOXIDANTS AND VITAMINS ON THE FUNCTION OF HUMAN CELLS IN VITRO - Dаnlybayeva G.A.; Akhmadeyeva , Z.T. (Eurasian Journal of Applied Biotechnology, 2016)
Cell culture is a major tool in biomedical research that has been developing since the middle of the last century. Healthy cells isolated from body tissues have specific requirements for the composition of artificial culture media. There are a number of synthetic growth media (for example, 199, 703 and Eagle), which contain amino acids, vitamins, and mineral salts, among other additives. Serum is added to all synthetic media, as the main source of growth factors, minerals and proteins, for the cultivation of high-grade cell cultures. In addition to standard synthetic media, there are a various specialised media for efficient propagation of cells with low proliferative potential; however, the high cost of these specialised media prohibits their use in mass-production applications. To obtain the required amount of material for experimental or commercial purposes, cell proliferation is usually necessary. A major factor in ensuring sufficient cell proliferation is the choice of optimal culture media, which may involve the use of cell-conditioned media, among various other components. Therefore, the addition of growth factors, antioxidants or vitamins to standard media (at non-physiological concentrations) can be very attractive. This article presents details of the effects of four antioxidants and vitamins on the viability, proliferation activity and expression of proteins in diploid cell culture. Our results reveal that addition of minimal non-toxic concentrations of vitamins and antioxidants to cell culture media has differing effects on the proliferation of continuous cell cultures, ranging from stimulation to suppression of cell proliferation.